Optimum Time of Insemination after Onset of Oestrus in Holstein – Friesian Dairy Cows in the Peri-urban Khartoum (Sudan) - Ador, Lino Libo; Nikhaila, Abdel Moneim Mukhtar Abu (Journal of Agricultural Studies, 2023)
The aim of this study was to determine the optimum time of insemination after onset of oestrus in Holstein-Friesian dairy cows. 146 and 92 Cows were randomly assigned to the control and prostaglandin F2α treated groups respectively. The experimental animals were then visually observed for oestrus for a period of twelve months. 188 and 99 inseminations were given to the control and prostaglandin F2α treated groups respectively. The inseminations were given at time intervals of 1-6, 7-12, 13-18, and 19-24 hours after onset of oestrus during winter, hot dry summer and hot wet summer. During the three seasons, inseminations were carried out in cows at postpartum interval of 41-60, 61-80, 81-100, 101-120, 121 and over days. The trial was conducted in Cows at parities 1 and 2 as a group, and parities 3 and over as a separate group. The optimum time of insemination to achieve the highest conception rates was at 13-18 hours in the control group of Cows. Winter had the highest conception rates compared to other seasons. Cows at postpartum intervals of 121 and over days had the highest conception rates. Conception rates in cows at parities 1 and 2 had the highest conception rate compared to other parities. The present study revealed that the control group of cows had the highest conception rates when inseminations were at 13 – 18 hours after onset of oestrus compared to prostaglandin F2α treated cows.